A Rare Complication of Acute Appendicitis: Superior Mesenteric Vein Thrombosis - Hendra Koncoro; Rafael Eddy Setijoso; Maisie ME Johan (The Indonesian Society for Digestive Endoscopy, 2016)
Superior mesenteric vein (SMV) thrombosis caused by acute appendicitis is quite rare nowadays. These conditions occurs secondary to infection in the region drained by the portal venous system. In this case, we report a successfully treated case of SMV thrombosis and liver abscess associated with appendicitis with antibiotics and anticoagulant.Early diagnosis and prompt treatment are basic to a favorable clinical course.